2017
DOI: 10.1186/s12907-017-0062-z
|View full text |Cite
|
Sign up to set email alerts
|

Solitary fibrous tumor occurring in the parotid gland: a case report

Abstract: BackgroundSolitary fibrous tumor is an uncommon spindle cell neoplasm of unknown origin. It has been reported in many anatomic sites, with a rare occurrence in the head and neck region. Solitary fibrous tumors of the parotid gland are exceptional; their clinical and radiologic features are non specific, often mimicking more common salivary gland tumors. Pathologic examination and immunohistochemistry are required to make the correct diagnosis. The prognosis is favorable, with most tumors being benign, and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Previous reports on color Doppler US of SFTs in the head and neck have shown that these tumors are usually vascular . In contrast, none of the abdominal SFTs examined by Hui et al showed internal vascularity.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Previous reports on color Doppler US of SFTs in the head and neck have shown that these tumors are usually vascular . In contrast, none of the abdominal SFTs examined by Hui et al showed internal vascularity.…”
Section: Discussionmentioning
confidence: 74%
“…On high‐resolution gray scale US, SFTs have been reported as well circumscribed and hypoechoic, similar to benign tumors that commonly occur in the salivary glands . SFTs may also appear as heterogeneous and polycyclic masses,indicating the presence of necrosis, hemorrhage, and cystic areas.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations